PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP UMUM PADA RUMAH SAKIT DAERAH MADANI PROVINSI SULAWESI TENGAH - Reyza PZ, Reyza PZ (Katalogis, 2017)
This research aims to identify and analyze the importance of service quality to meet the expectation of patients and its effect on inpatients satisfactions in Madani Regional Hospital of Central Sulawesi. The research applies qualitative-quantitative approach with Importance-Performance Analysis (IPA) Method and multiple linear regressions by employing proportionate startified random sampling thecnique. Quadrant A in IPA Method, indicated by low performance and high importance is occupied by nurses’ attention, doctor’s attention, understanding patients wishes, service time, and hospital security. Quadrant B indicated by high performance and high importance is occupied by medical staff’s neatness, medical staff hygiene, and communications easiness. Quadrant C indicated by low performance and low importance is occupied by parking lot space, parking arrangement, and rooms clealiness. Quadrant D indicated by high performance and low importance is occupied by the beauty of the hospital’s building design. Multiple linear regressions analysis shows that service quality includes physical evidence, emphaty, responsiveness, reliability, and assurance simultaneously have significant effect on inpatients satisfactions with fsig of 0.000. Partially, physical evidence with tsig of 0.048 and assurance with tsig of 0.018 have significant effect on inpatients satisfaction, while emphaty with tsig of 0.900, assurance with tsig of 0.220, and reliability with tsig of 0.688 have insignificant effect on inpatients satisfactions.